2005
DOI: 10.1111/j.1523-1755.2005.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption in the kidney: Effects of nitric oxide synthase isoforms and angiotensin II

Abstract: In patients with chronic kidney disease, metabolic acidosis can occur as a result of insufficient ammoniagenesis within the damaged kidney. This, in turn, can bring about a variety of sequella that have their basis in hormonal and cellular abnormalities that effect stunted growth, loss of muscle and bone mass, and negative nitrogen balance. Cellular mechanisms accounting for these findings are reviewed. In bone, metabolic acidosis causes direct dissolution of bone; ostoeclastic activity is increased while oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 51 publications
3
81
1
1
Order By: Relevance
“…Therefore, NOS inhibition has more impact on inducing hypoxia in tubular segments of the medulla than of the cortex. Besides, Deng et al showed that NOS inhibition decreased the efficiency of tubular respiration in isolated proximal tubules,43 whereas the proximal tubules are the most efficient tubules in Na + reabsorption. NOS inhibition also reduced total reabsorption of Na + in proximal tubules 44.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NOS inhibition has more impact on inducing hypoxia in tubular segments of the medulla than of the cortex. Besides, Deng et al showed that NOS inhibition decreased the efficiency of tubular respiration in isolated proximal tubules,43 whereas the proximal tubules are the most efficient tubules in Na + reabsorption. NOS inhibition also reduced total reabsorption of Na + in proximal tubules 44.…”
Section: Discussionmentioning
confidence: 99%
“…When Na ϩ reabsorption mechanisms are activated under experimental observations, an increased O 2 consumption is normally observed in the kidney (43). However, intravenous perfusion of amino acids in healthy men has not shown to change the O 2 basal levels in the kidney (44).…”
Section: Discussionmentioning
confidence: 99%
“…Kidneys of L-NAME-treated rats had fewer normal glomeruli and fewer vasculatures in the cortex, outer medulla, and inner medulla; losartan normalized the values to control levels, suggesting that a generalized rarefaction of renal capillaries by chronic NOS inhibition is mediated by ANG II through AT 1 receptors (Fortepiani et al, 2003). L-NMMA and the nNOS inhibitor S-methyl-L-thiocitrulline decreased rat renal blood flow, but L-NA plus losartan did not; L-NMMA increased metabolic efficiency in the kidneys of control and losartan-treated rats, and the nNOS inhibitor also increased metabolic efficiency and mitochondrial oxygen consumption in proximal tubules (Deng et al, 2005). It seems that nonselective NOS inhibition increases the oxygen costs of kidney function independently of ANG II and that kidney nNOS is responsible for these in vivo and in vitro effects.…”
Section: Other Vasculaturesmentioning
confidence: 95%